Association Of The Storage Age Of Trasfused RBC With Adverse Outcomes In Post Cabg Patients At Hospital Serdang - Omar, Norkhazarina (2019)
Background: Extended storage time lead to storage lesion changes in red blood cells (RBCs) that can possibly cause harmful effects to recipients. Currently, there was no established guideline available to suggest transfusion of fresher RBCs had any advantages over older RBCs in clinical outcomes among cardiac surgical patients. In this study, adverse outcomes in post coronary artery bypass grafting (CABG) patients who received different storage age of RBCs were analysed Methods: This was an observational retrospective study done in Hospital Selayang. Data from patients who underwent CABG within one year were collected. Subjects were allocated into three groups according to the storage age of RBCs that they received; ≤ 14 days, >14 days and mixed. The effect of RBCs storage age on various post-operative outcomes were analysed using multivariable analysis with significant p<0.05. Comparison total unit of RBCs transfused between the three storage ages of RBCs was also studied using One-way ANOVA test. Results: A total of 253 patients who received 954 RBCs units were analysed. Subjects were; n = 62 in group of RBCs ≤ 14 days, n = 99 in group of RBCs >14 days and n = 92 in mixed group. There were no association of any of the groups of RBCs storage ages with post CABG adverse outcomes. Patients transfused with greater unit of RBCs more likely to receive mixed variance storage age of RBCs. Conclusion: The duration of RBCs storage was not associated with significant differences in adverse outcomes among post CABG patients.